Preparation of labor market for the industry 4.0 focusing on the Russian labor market - Kurnikova, Vasilisa; Kašparová, Eva, 1958-; Černá, Daniela; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2020)
The thesis investigates the concept of labor market 4.0 and its specifics on the present stage. The findings of the research combine both a theoretical overview of the concept and its inherent characteristic and a case-study analysis of labor market 4.0 as implemented in Gazprom, Russia’s monopolist corporation on the energy market. It is shown that basic elements of labor market 4.0 such as automated data collection and processing, big data analytics, the Internet of Things, cloud technologies, and so on play an important role in the optimization of human resource management in the business practices of companies. Practical recommendations have been developed for Gazprom to improve further the integration of labor market 4.0 into the corporation’s business.
Vedoucí práce: Eva Kašparová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: business administration/corporate finance and management [obor bakal. práce]; bakalářské práce; bachelor's theses